EFFECT OF EDUCATION LEVEL, GENDER ROLE, AND INFORMATION TECHNOLOGY ON MSME INCOME IN THE ERA OF COVID-19 (CASE STUDY ON FOOD MSMES IN BANDUNG CITY) - Tuti Anggraeni; Ratih Hurriyati; Puspo Dewi Dirgantari; Dodi Sukmayana (UNIVERSITAS PAKUAN, 2022)
The specific purpose of this study is to provide an overview to the food sector SMEs in the city of Bandung, that the influence of education level, gender roles, and information technology has a significant influence on their income. This study used 59 samples of food sector MSME business actors in the Bandung City area. The sampling technique chosen in this study was incidental sampling technique and data collection using questionnaires distributed to respondents, namely MSME owners. The data analysis technique used in this research is multiple linear regression. The results showed that there was an influence of education level, gender roles, and information technology on the income of MSME actors in the food sector in the city of Bandung. Hopefully this research can provide input to the food sector MSME administrators in the Bandung Raya area, especially the food sector MSME actors to continue to improve the quality of education both through formal and non-formal education, increase the existence of gender roles by not leaving their nature as women, and continue to upgrade information technology. which is useful for marketing the results of his business. Because based on research conducted by researchers, these three variables can increase the income of MSME actors.